2021
DOI: 10.1016/j.ijid.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Nodding syndrome research revisited

Abstract: Nodding syndrome is one of several forms of onchocerciasis-associated epilepsy (OAE) seen among children in areas formerly hyperendemic for the transmission of Onchocerca volvulus. These forms of epilepsy are highly prevalent and clustered in certain villages located close to blackfly (Diptera: Simuliidae) breeding sites. OAE presents with a wide spectrum of seizures, including generalized tonicclonic and head nodding seizures, impaired cognitive function, growth stunting and delayed puberty. In 2014, the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…NS is a devastating childhood neurological disorder, which is characterized by pathological nodding seizures and multiple additional brain pathologies [ 2 , 3 , 4 , 8 , 9 , 21 ]. The affected children experience a complete and permanent stunting of growth and mental handicap [ 2 , 3 , 4 , 7 , 8 ]. While NS is still enigmatic, it is strongly associated with the parasitic worm OV [ 1 , 5 , 8 , 9 , 15 , 16 , 17 , 18 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…NS is a devastating childhood neurological disorder, which is characterized by pathological nodding seizures and multiple additional brain pathologies [ 2 , 3 , 4 , 8 , 9 , 21 ]. The affected children experience a complete and permanent stunting of growth and mental handicap [ 2 , 3 , 4 , 7 , 8 ]. While NS is still enigmatic, it is strongly associated with the parasitic worm OV [ 1 , 5 , 8 , 9 , 15 , 16 , 17 , 18 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The affected children experience a complete and permanent stunting of growth and mental handicap [ 2 , 3 , 4 , 7 , 8 ]. While NS is still enigmatic, it is strongly associated with the parasitic worm OV [ 1 , 5 , 8 , 9 , 15 , 16 , 17 , 18 , 53 ]. Recently, it was shown that autoimmunity might drive the pathology of this disease [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations